One-dimensional analysis of thermoelement exposed to lateral heat transfer as a wall in MEMS-based thermoelectrically controlled micronozzle - Hameed, Ammar; Kafafy, Raed; Idres, Moumen (Inderscience Publishers, 2012)
Two thermoelements are formed as walls of a micronozzle to perform heating-cooling on a gas flowing between them. The model of heat transfer by conduction opposites to Peltier effect is built, including Joule heating, Seebeck effect and heat dissipation to the flowing gas. A general energy equation of one-dimensional heat flow in a TE subjected to electrical field and heat convection at the lateral side is developed and solved both analytically and numerically. The effects of varying the convection heat transfer coefficient, Joule heating and boundary conditions are tested for constant material properties using the analytical solution. Two parameters which play important roles in the thermal performance of TE are identified; heat resistance ratio and energy growing ratio. The effects of varying these two parameters as well as TE geometry have been investigated thoroughly, and the results are presented in the form of charts to assist the design and material selection of the TE